An empirical analysis of exports between Malaysia and TPP member countries: Evidence from a Panel Cointegration (FMOLS) model - Zainal Abidin, Irwan Shah; Abu Bakar, Nor'Aznin; Haseeb, Muhammad (Canadian Center of Science and Education, 2014)
The aim of this study is to investigate empirically the role of Malaysian exports to TPP countries towards economic growth of Malaysia from 1997 to 2012.The results of this study confirm that Malaysian exports to TPP countries contribute in economic growth of Malaysia.Therefore, the result of this study is obtained through the empirical investigation of the model.Mainly, empirical investigation is based on FMOLS model but some preliminary tests are also performed.The results of unit root test presents that all Variables are non-stationary at level I(0) and become stationary after first difference I(1).In addition, results of Kao’s panel cointegration shows that all the variables are cointegrated. Furthermore, Results of FMOLS confirms that out of all the variables included in the model, GDP, TRGDP and ER have significant effect on the exports. ECM panel unit root test were applied to confirm the stability of FMOLS. According to the unit root test of the residuals of FMOLS model, it can be confirmed that the long run results are not spurious.Results of Panel ECM show that out of all variables GDP and TRGDP are positively effect on exports.Finally, results of Granger Causality show that only CPI, GDP and TRGDP are cause exports in Malaysia.The government of Malaysia through understood the importance of exports with TPP member countries to boost economic growth.The latter not only contributes to economic growth through capital formation but also promotes trade activity by making financial resources available at lower cost; attracting foreign direct investment as well as facilitating development of advanced technology. Moreover, this study not only contribute to the exports and economic growth literature but also will guide the policy maker to chalk out right, effective and appropriate policy in order to improve exports between Malaysia and TPP countries.